2023
DOI: 10.2147/jmdh.s433813
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging a Synergy in Motivation to Effect Job Satisfaction of Healthcare Professionals in Public Blood Bank Units: A Cross-Sectional Study

Marko Slavkovic,
Dragan Eric,
Marija Miric
et al.

Abstract: Background Superior patient care requires a team of medical professionals who are motivated and satisfied with their jobs. However, in an occupational setting characterized by prolonged work hours and excessive stress, managers face increased challenges in their attempts to motivate employees and sustain high levels of job satisfaction. Aim This study investigates whether, and to what extent, extrinsic and intrinsic motivation might predict job satisfaction. It also exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The research model includes the social dimension, which in earlier studies was often neglected and not included in any consideration [46]. Healthcare organizations face several challenges [18], especially in the area of motivation [74], as well as attracting, recruiting, and selecting employees, with a distinct deficit in most countries. This further indicates the importance of the social dimension for the sustainability of healthcare organizations, which comprises very significant aspects related to people in the organization [49].…”
Section: Discussionmentioning
confidence: 99%
“…The research model includes the social dimension, which in earlier studies was often neglected and not included in any consideration [46]. Healthcare organizations face several challenges [18], especially in the area of motivation [74], as well as attracting, recruiting, and selecting employees, with a distinct deficit in most countries. This further indicates the importance of the social dimension for the sustainability of healthcare organizations, which comprises very significant aspects related to people in the organization [49].…”
Section: Discussionmentioning
confidence: 99%
“…In both male and female groups, extrinsic motivation significantly influences intrinsic motivation, but this influence is slightly stronger in men. Moreover, intrinsic motivation significantly affects job satisfaction in men but not in women [ 28 ]. In addition, another study revealed that there was a stronger positive correlation between professional opportunities and motivation among younger employees compared to their older counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings, other studies revealed relationships among variables across various sample characteristics like gender, age, job position, and employment status. Extrinsic motivation predicts higher intrinsic motivation and job satisfaction, with intrinsic motivation mediating this relationship, along with factors such as gender, age, job position, and employment status [ 28 ]. This could be thought to be related to workers’ work–life experiences and how cultural norms, heightened expectations in particular institutional settings, and government support for the work–life balance affect the nature of the work interface [ 34 ].…”
Section: Discussionmentioning
confidence: 99%